Deficits in neuromuscular control of the trunk predict knee injury risk: A prospective biomechanical-epidemiologic study - Zazulak, B. T.; Hewett, T. E.; Reeves, N. P.; Goldberg, B.; Cholewicki, J. (The American Journal of Sports Medicine, 2007)
Female athletes are at significantly greater risk of anterior cruciate ligament (ACL) injury than male athletes in the same high-risk sports. Decreased trunk (core) neuromuscular control may compromise dynamic knee stability.